Noninvasive Evaluation of Coronary Perfusion by Transthoracic Doppler Echocardiography in Patients with Anterior Myocardial Infarction before Coronary Intervention - Malla, Sabindra Bhupal; Haque, Mostashirul; Osmany, DMMF; Parvin, Tanjima; Safiuddin, Mohammad; Banerjee, Sajal Krishna; Ahsan, Syed Ali; Ahmed, Chaudhury Meshkat; Md Iqbal, Khaled (University Heart Journal, 2019)
Background: Transthoracic Doppler Echocardiography (TTDE) has made a breakthrough in noninvasive evaluation of coronary artery flow, especially in the distal left anterior descending coronary artery (LAD). The present study was intended to test the hypothesis whether TTDE can differentiate coronary perfusion with Thrombolysis in Myocardial Infarction (TIMI) grade 3 from TIMI grade ≤2 in patients with anterior myocardial infarction (AMI). Methods: A total of 30 consecutive patients suggestive of anterior MI including those who received thrombolysis with the potential need for Percutaneus Coronary Intervention (PCI) were enrolled in the study. The coronary perfusion was evaluated by antegrade flow visualization in distal LAD by Colour TTDE and antegrade flow velocity measured by pulsed TTDE followed by coronary angiogram for TIMI grade flow in culprit artery. The sensitivity, specificity and diagnostic accuracy were determined by comparing TTDE parameters with angiographic TIMI flow grade. Results: The antegrade distal LAD flow visualization by Color TTDE enabled differentiation of TIMI 3 from TIMI ≤2 with a sensitivity, specificity, PPV, NPV and diagnostic accuracy of 100%, 62.5%, 40%, 100% and 70% respectively. The Receiver Operating Characteristic (ROC) curve constructed to find the cut-off value for antegrade flow velocity in distal LAD in differentiating TIMI 3 from TIMI 0-2 was found to be 30.5 cm/ s with an area under the curve being 0.893, p =0.011. The antegrade flow velocity in distal LAD e” 30.5 cm/s by pulsed TTDE had a fair sensitivity (66.7%) , but had high specificity (100%) and overall diagnostic accuracy (86.7%). Conclusion: The study concluded that antegrade distal LAD flow visualization by Color TTDE can fairly differentiate TIMI 3 from TIMI ≤2 with high sensitivity, and moderate specificity and diagnostic accuracy. Additionally, the antegrade flow velocity in distal LAD by pulsed TTDE has a moderate sensitivity and high specificity to predict the angiographic TIMI flow grade. Thus, TTDE enables noninvasive differentiation of coronary perfusion in patients with anterior MI before coronary intervention. University Heart Journal Vol. 15, No. 1, Jan 2019; 22-27